Cross-Platform Engineering and Enterprise Integration in Healthcare Information Systems: A Comprehensive Review - Pooja Chitrakar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the critical role of cross-platform engineering and enterprise integration in revolutionizing healthcare information systems. It examines the current landscape of healthcare software solutions, including Electronic Health Records (EHRs), Picture Archiving and Communication Systems (PACS), Laboratory Information Systems (LIS), and Remote Patient Monitoring tools. The article delves into the challenges of interoperability and presents solutions through standardized APIs, middleware, and microservices architectures. It discusses the importance of end-to-end connectivity and explores standardization frameworks like HL7 FHIR and DICOM. The article also evaluates the impact of these integrations on patient outcomes, telehealth capabilities, operational efficiency, and data security. A case study on implementing a hybrid architecture for EHR systems provides practical insights into the benefits and challenges of such integrations. Finally, the paper looks at future directions, emerging technologies, potential barriers to adoption, and research opportunities in the field of healthcare integration. Throughout, the article emphasizes the transformative potential of integrated healthcare systems in creating a more connected, secure, efficient, and patient-centric healthcare ecosystem.